2018
DOI: 10.1080/10790268.2018.1452389
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional outcomes in traumatic spinal cord injury with rehabilitation-acquired urinary tract infections: A retrospective study

Abstract: Objective The objective of this study was to evaluate the impact of urinary tract infections (UTIs) acquired during acute inpatient traumatic Spinal Cord Injury (tSCI) rehabilitation on Functional Independence Measure (FIM) gains. Design Retrospective chart review of consecutive patients with tSCI admitted to an acute rehabilitation facility from 2007-2012. The primary outcome was FIM scores and the association with UTI. Results The sample included 110 patients and 70 acquired UTIs. No demographic differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Urinary tract infections are a common source of morbidity among patients undergoing rehabilitation for spinal cord injuries [23]. Moreover, studies of patients undergoing neurorehabilitation for stroke, brain, and spinal cord disorders have demonstrated that decreased functional scores are associated with urinary tract infections [29][30][31]. In our study, there was no statistical significance in the functional scores between the patients with and without acute urinary dysfunction (see Table 1).…”
Section: Discussioncontrasting
confidence: 54%
“…Urinary tract infections are a common source of morbidity among patients undergoing rehabilitation for spinal cord injuries [23]. Moreover, studies of patients undergoing neurorehabilitation for stroke, brain, and spinal cord disorders have demonstrated that decreased functional scores are associated with urinary tract infections [29][30][31]. In our study, there was no statistical significance in the functional scores between the patients with and without acute urinary dysfunction (see Table 1).…”
Section: Discussioncontrasting
confidence: 54%
“…Interestingly, a study from the United State found a statistically significant correlation between acquired UTIs and lower Functional Independence Measure motor scores on admission, gain, and discharge in traumatic SCI rehabilitation. 31 Independence in performing activities depends not only on SCI's level and severity but also on early access to an inpatient postacute SCI rehabilitation program by SCI specialized rehabilitation teams. 32 A recent study in Thailand confirmed that admission for inpatient postacute rehabilitation to an SCI specialized rehabilitation facility is a predictive factor of better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The FIM consists of 18 scored items divided into motor and cognitive subscales 9 . Administration of the FIM at admission may vary by facility 10 . Following hospital protocol, the minimal score on total FIM is 18 (total assistance), and the maximum score is 126 (complete independence) 9 .…”
Section: Methodsmentioning
confidence: 99%
“…9 Administration of the FIM at admission may vary by facility. 10 Following hospital protocol, the minimal score on total FIM is 18 (total assistance), and the maximum score is 126 (complete independence). 9 Although minimal clinically important difference (MCID) has not been established for SCI, in an acute stroke population, MCID is 22 points for total FIM, 17 points for FIM motor subscale, and 3 points for cognitive subscale.…”
Section: Outcome Measurementioning
confidence: 99%